Hemoglobinopathy detection through an institutional neonatal screening program in Colombia - Sandra Johanna Echeverry-Coral; Claudia Carolina Colmenares-Mejía; Zuli Ximena Yepes-Molina; Oscar Martínez-Nieto; Mario A. Isaza-Ruget
ABSTRACT Introduction: Hemoglobinopathies are among the most common genetic disorders of hemoglobin worldwide and a public health problem. In Colombia, even though geographical areas with high incidence of this disorder have been reported, the absence of a national screening program does not permit us to determine its prevalence. Objective: Establish the prevalence of hemoglobin variants in a population covered by the neonatal screening program of Clínica Colsanitas S.A., between June 2000 and December 2014, including eight capital cities in Colombia. Methods: A retrospective cross-sectional study was conducted. We collected data from reports of the neonatal hemoglobinopathy-screening program for full-term newborn babies between 5 and 15 days old. Qualitative hemoglobin analysis was performed using gel electrophoresis of blood samples taken from the babies' heels. Results: The overall prevalence of abnormal Hb was 1.3%. Within the groups of newborns affected with any hemoglobinopathy (n = 400), the most frequent abnormal structural hemoglobins found were HbS (43%), HbC (9%), fast Hb (8%). For quantitative hemoglobins, HbA2 was 3.7% and HbA kept slightly elevated in 14.7% of cases. Frequency of homozygosis for HbS was 0.01%. Barranquilla, Cartagena and Cali were the cities with the greatest frequency of hemoglobinopathies. No correlation between sex and abnormal hemoglobin was found. Discussion and conclusion: Taking in consideration data from the World Health Organization (WHO) on hemoglobinopathies, our prevalence of > 1% is considered high. Therefore, a more extended coverage and the need for a national screening program are priorities.